PEDIATRIC ROTARY FILES FROM KEDO-S PLUS FRACTURE INCIDENCE: A PROSPECTIVE CLINICAL STUDY (Journal of Pharmaceutical Negative Results, 2023)
INTRODUCTION: This clinical study's main objective was to investigate the likelihood that an instrument fracture would occur during the preparation of primary molar root canals using Kedo - S Plus rotary files.MATERIALS AND METHODS: 3 months and a standardized protocol were used to treat 100 primary molars on the mandible and maxilla (335 root canals). Kedo-S Plus file was used for mechanical preparations that were carried out in accordance with the manufacturer's recommendations. Each instrument in Group A assisted in the management of three cases, as opposed to Groups B, C, and D assisted in the management of five, nine, and twelve cases, respectively. After being removed from the canal, the rotary files were examined under an operating microscope. Descriptive statistics were used once the numbers were tabulated.RESULTS: One fracture of the Kedo S plus file was discovered (1%), and it happened in group D in the mesiobuccal canal's apical third of a maxillary molar.CONCLUSION: The present research indicates that Kedo-S Plus rotary files fracture less frequently. The most likely places for the instrument to separate are the apical portion of the root canals and the buccal canal of the maxillary second molar.